Algorithm of a new variational inclusion problem and strictly pseudononspreading mapping with application - Wongvisarut Khuangsatung; Atid Kangtunyakarn (My University, 2014)
The purpose of this research is to modify the variational inclusion problems and prove a strong convergence theorem for finding a common element of the set of fixed points of a κ-strictly pseudononspreading mapping and the set of solutions of a finite family of variational inclusion problems and the set of solutions of a finite family of equilibrium problems in Hilbert space. By using our main result, we prove a strong convergence theorem involving a κ-quasi-strictly pseudo-contractive mapping in Hilbert space. We give a numerical example to support some of our results.
Keywords: Differential inclusion; Optimization and Variational Analysis